2008
DOI: 10.1523/jneurosci.2225-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Enhancement of Dopamine Transmission within the Nucleus Accumbens Shell by Cocaine Is Attributable to a Direct Increase in Phasic Dopamine Release Events

Abstract: Preferential enhancement of dopamine transmission within the nucleus accumbens (NAc) shell is a fundamental aspect of the neural regulation of cocaine reward. Despite its importance, the nature of this effect is poorly understood. Here, we used fast-scan cyclic voltammetry to examine specific transmission processes underlying cocaine-evoked increases in dopamine transmission within the NAc core and shell. Initially, we examined altered terminal dopamine concentrations following global autoreceptor blockade. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
258
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(289 citation statements)
references
References 85 publications
27
258
2
1
Order By: Relevance
“…This preferential action has been initially documented by microdialysis studies in acutely experimenter-administered rats (Aragona et al, 2008;Pontieri et al, 1995) and later demonstrated in rats during acquisition of i.v. cocaine SA (Lecca et al, 2007a).…”
Section: Introductionmentioning
confidence: 74%
“…This preferential action has been initially documented by microdialysis studies in acutely experimenter-administered rats (Aragona et al, 2008;Pontieri et al, 1995) and later demonstrated in rats during acquisition of i.v. cocaine SA (Lecca et al, 2007a).…”
Section: Introductionmentioning
confidence: 74%
“…29 Indeed, while these regions are just a few hundred micrometers apart, voltammetry studies show that their neurochemical activation to cues and drugs varies substantially. 30,31 We cannot rule out DA hot spots within either nucleus without more extensive mapping as has been suggested by voltammetry studies. 51 The results also suggest greater 5-HT activity in core than shell.…”
Section: Acs Chemical Neurosciencementioning
confidence: 91%
“…This was done so that, during optical manipulations as part of the extinction experiment, 20 s periods of inhibition were linked with specific lever presses and to ensure that no lever presses could occur during the inhibition period. This time period of inhibition was chosen because prior work indicated that an intravenous cocaine infusion requires Ïł10 s to increase dopamine levels in the brain and that this increase can persist up to 20 s (Aragona et al, 2008). Therefore, we considered it likely that neural encoding regarding the lever press and lack of reinforcer may persist up to 20 s after the press.…”
Section: Cocaine Self-administration and Extinctionmentioning
confidence: 99%
“…Moreover, evidence suggests that the IL actively suppresses cocaine seeking after lever pressing is extinguished. IL inactivation and activation after extinction training induces cocaine seeking and suppresses cued and cocaine-induced reinstatement, respectively (Peters et al, 2008;LaLumiere et al, 2012). Akin to the results with self-administration, optical inhibition of pyramidal neurons in vmPFC impairs extinction learning for cocaine conditioned place preference (Van den Oever et al, 2013).…”
Section: Introductionmentioning
confidence: 99%